A retrospective study on efficacy of the ERAS protocol in patients undergoing surgery for Crohn disease: A propensity score analysis. Issue 6 (June 2020) - Mineccia, Michela; Menonna, Francesca; Germani, Paola; Gentile, Valentina; Massucco, Paolo; Rocca, Rodolfo; Ferrero, Alessandro
Abstract: Background: Enhanced Recovery After Surgery (ERAS) offers many benefits for patients with colorectal cancer. However, its application to patients with Crohn's disease (CD) is questioned. Aim: The aim of this propensity-matched study was to validate the results of ERAS protocol on CD patients. Methods: Patients undergoing ileocolic resection for primary or relapsed CD from 2007 to 2018 were retrospectively analyzed and propensity-matched into two equal groups (ERAS vs standard of care). Demographic characteristics, length of stay, bowel function, oral intake, and perioperative morbidity were analyzed. Results: Ninety four out of 299 patients were selected for analysis. No significant difference was observed for age, gender, American Society of Anesthesiologists score, body mass index, previous surgery and therapy, operative time and laparoscopy. The median length of stay in ERAS and non-ERAS groups was 6 and 8 days ( p  < 0.001). Median postoperative days of first bowel movement and solid oral intake were day 1 and day 2 p  < 0, 001, and day 2 and day 4.5 p <  0, 001 in ERAS and non-ERAS group, respectively. No statistically differences in other postoperative outcomes were shown. Conclusions: ERAS implementation showed decreased length of stay, faster bowel function restoration and earlier solid oral intake in patients who underwent laparoscopic or open ileocolic resection for primary or relapsing CD.